2018
DOI: 10.1038/s41598-018-31731-9
|View full text |Cite
|
Sign up to set email alerts
|

Habitat environments impacted the gut microbiome of long-distance migratory swan geese but central species conserved

Abstract: The gut microbime plays an important role in the health of wild animals. This microbial community could be altered by habitat pollution and other human activities that threaten the host organisms. Here, we satellite-tracked a flock of swan geese (Anser cygnoides) migrating from their breeding area (Khukh Lake, Mongolia), with low levels of human activity, to their wintering area (Poyang Lake, China) which has been heavily impacted by human activities. Twenty fecal samples were collected from each site. High-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 67 publications
8
83
0
Order By: Relevance
“…Within the primate clade, similar patterns have been described in the Chlorocebus genus (Trosvik et al, ), Alouatta pigra (Amato et al, ), Lemur catta (Bennett et al, ), and Procolobus gordonorum (Barelli et al, ). GM robustness to habitat disturbance has been reported in parrots ( Strigops habroptilus ; see Perry, Digby, & Taylor, ), but other taxa, including frogs ( Fejervarya limnocharis ; see Chang, Huang, Lin, Huang, & Liao, ), jackals ( Canis mesomelas ; see Menke et al, ), and swan geese ( Anser cygnoides ; see Wu et al, ) show that populations in disturbed habitats exhibit distinct GMs relative to pristine habitat counterparts. While our findings in V. variegata generally fit this narrative, our results indicate that it is not simply the level of habitat disturbance driving GM diversity.…”
Section: Discussionmentioning
confidence: 92%
“…Within the primate clade, similar patterns have been described in the Chlorocebus genus (Trosvik et al, ), Alouatta pigra (Amato et al, ), Lemur catta (Bennett et al, ), and Procolobus gordonorum (Barelli et al, ). GM robustness to habitat disturbance has been reported in parrots ( Strigops habroptilus ; see Perry, Digby, & Taylor, ), but other taxa, including frogs ( Fejervarya limnocharis ; see Chang, Huang, Lin, Huang, & Liao, ), jackals ( Canis mesomelas ; see Menke et al, ), and swan geese ( Anser cygnoides ; see Wu et al, ) show that populations in disturbed habitats exhibit distinct GMs relative to pristine habitat counterparts. While our findings in V. variegata generally fit this narrative, our results indicate that it is not simply the level of habitat disturbance driving GM diversity.…”
Section: Discussionmentioning
confidence: 92%
“…These are interesting observations considering the hypothesis of environmentally‐ and diet‐derived colonization of the gut microbiome. In addition to humans, in which perinatal factors are believed to play an important role in microbiome seeding (Dominguez‐Bello et al, ), other organisms are reported to have significant seeding from the habitat they live in, including marine organisms (Chen, Chen, Weng, Shaw, & Wang, ), birds (Wu et al, ), and soil‐dwelling arthropods (Degli Esposti & Martinez Romero, ).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of gut microbiota are mainly determined by their composition, which is affected by various factors such as host genetic background, health condition, social behaviour and habitat environment factor [17][18][19][20][21][22][23][24]. Because of the importance of gut microbiota and other microbiome communities, some scientists suggest that the host and its microbiomes are considered as a biological unit subjected to natural selection [25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that ruminants depend heavily on gut microbiota to digest fibre in the rumen and use products such as short-chain fatty acids (SCFAs) to meet their energy needs [14,15]. Panda, which do not have a rumen, also rely on their microbiome to degrade hemicellulose and starch in bamboo [16].The functions of gut microbiota are mainly determined by their composition, which is affected by various factors such as host genetic background, health condition, social behaviour and habitat environment factor [17][18][19][20][21][22][23][24]. Because of the importance of gut microbiota and other microbiome communities, some scientists suggest that the host and its microbiomes are considered as a biological unit subjected to natural selection [25].…”
mentioning
confidence: 99%